Pengaruh Kualitas Pelayanan SCO (Sales Counter Officer) Terhadap Kepuasan Pelanggan Pada CV Express Mentari - Rudy Irwansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The purpose of this study is to see customer satisfaction with the service quality of the SCO (Sales Counter Officer) section, this research was conducted by asking customers to be willing to fill customer satisfaction questionnaires which later the questionnaire was entered into the comment box, sampling was aimed at only as many as 100 people who will be a respondent as well as information in qualitative research and the results of these objectives can show that the services provided by the SCO (Sales Counter Officer), have met the overall satisfactory standards and will later foster relationships created by the good service that has been provided by SCO (Sales) employees Counter Officer) give. The importance of maintaining service quality also affects the sustainability of the company EXPRESS MENTARI in the future.